(untitled) (Archaeologia Adriatica, 2017)
Supported by the Municipality of Ližnjan, the International Center for Underwater Archaeology launched in 2012 the underwater archaeological investigation of three shipwrecks at Cape Uljeva on Istria’s southeastern coast. Cape Uljeva closes the spacious Kuje Cove on its southern side. While most of the cargo from ancient shipwrecks has been pillaged in time, numerous fragments can still be found in situ, enabling the research and reconstruction of the shipwrecks. The investigation started with mapping the crevices and hollows on the rocky seabed containing archaeological remains in order to document the distribution of the finds. For the time being, the first shipwreck (Uljeva A) is dated to the 1st century BC and the second one (Uljeva B), perhaps to the 4th century AD.